(untitled) (Journal of Geography and Environmental Management, 2018)
The article discusses the causes of inadequate development of tourism in Kazakhstan and the need for the country’s system of scientific support for its development and territorial organization. The three main objectives of the establishing modern high-performance tourism industry are analyzed. In particular, the necessary restructuring of tourism management at the state level and the real support of tourism as a promising sector from the State. The second important task is the development of the tourism science and scientific support for the implementation of the System tourism development plans in Kazakhstan, including the territorial organization and infrastructure development. And the third – personnel training, including scientific and pedagogical, capable of ensuring the competitiveness of Kazakhstan’s tourism on the international market.